2016
DOI: 10.3233/wor-152174
|View full text |Cite
|
Sign up to set email alerts
|

Work experiences among attendees of day centres for people with psychiatric disabilities

Abstract: Link to publicationCitation for published version (APA): Eklund, M., & Sandlund, M. (2016). Work experiences among attendees of day centres for people with psychiatric disabilities. Work (Reading, Mass.), 53(2), 377-385. DOI: 10.3233/WOR-152174 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The study draws conclusions at two levels. First, it concludes that women and men are doing gender to some extent, in terms of choosing and engaging in activities, but less than one could expect from previous research on former employments in the study group where clear gender patterns were discerned (Eklund and Sandlund, Forthcoming). This may partly be explained by the lack of statistical discrimination; in day centers, as opposed to the open labor market employments, attendees can choose among tasks and activities they find stimulating and meaningful.…”
Section: Conclusion: Doing or Undoing Gender?mentioning
confidence: 72%
See 2 more Smart Citations
“…The study draws conclusions at two levels. First, it concludes that women and men are doing gender to some extent, in terms of choosing and engaging in activities, but less than one could expect from previous research on former employments in the study group where clear gender patterns were discerned (Eklund and Sandlund, Forthcoming). This may partly be explained by the lack of statistical discrimination; in day centers, as opposed to the open labor market employments, attendees can choose among tasks and activities they find stimulating and meaningful.…”
Section: Conclusion: Doing or Undoing Gender?mentioning
confidence: 72%
“…Interestingly, a study investigating previous work experiences among people with mental illness found that women more often had previous work experience in clerical and service occupations and that craft work and machine operators were more commonly previous occupations among the men (Eklund and Sandlund, Forthcoming). Consequently, it may be that the employment market is more gendered than the day center activities are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A psychiatric disorder may lead to a psychiatric disability, defined as having a mental illness that prevents the person from participating in society and leading a satisfactory and independent everyday life and that the condition has lasted for a considerable time (>2 years) [11]. Open-market employment is very rare in this group [12] and it is a responsibility of the municipalities in Sweden to organize communitybased psychiatric services so that people with psychiatric disabilities can receive the support they need in terms of meaningful daily activities. Day centres that provide such services are not only found in Sweden [13], but also in other parts of Europe [14,15], in the United States [16], in Canada [17] and in Australia [18].…”
Section: Introductionmentioning
confidence: 99%
“…Tjörnstrand and colleagues [15] found that the activities could be graded so that the level of demands needed to perform the activity could be suited to the attendee’s needs and capacities. Swedish guidelines state explicitly that day centers should strengthen the attendees’ work capacity [16] and similar goals are found in international research where the users themselves express their needs and goals [3, 10, 17]. In order to follow whether efforts aimed at increasing attendees’ engagement in day center activities are successful, a screening tool that could be used by staff or researchers for evaluation purposes would be useful.…”
Section: Introductionmentioning
confidence: 99%